The Effectiveness of John Holland's Career Counseling Theory using Imitation Techniques to Improve Self-Understanding and Career Decision-Making in Students at SMA Negeri 2 Ruteng-Purang - Jiman, Maria Pepin; Ketut Dharsana (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The low level of self-understanding and students’ inability to make appropriate career decisions remain significant issues in school guidance and counseling services. This condition often results in career choices that are misaligned with students’ personal potentials. This study aims to analyze the effectiveness of John Holland's career counseling theory using the imitation technique to enhance students' self-understanding and career decision-making. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The population consisted of 120 tenth-grade students, with a sample of 60 students selected through purposive sampling. Data were collected through questionnaires, interviews, and observations, while data analysis was conducted using multivariate testing. The results showed a significance value of 0.001 < 0.05 in the multivariate test, indicating that the implementation of John Holland's career counseling with the imitation technique was significantly effective in improving students’ self-understanding and career decision-making abilities. The implications of this study contribute to the development of guidance and counseling services in schools, assisting counselors in designing appropriate counseling interventions to optimize students’ self-potential and career decision-making skills.